2019
DOI: 10.1016/j.bbmt.2019.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Drugs as a Frequent Cause of Acute Rash in Patients after CD34+-Selected Peripheral Blood Stem Cell Transplantation

Abstract: Although histopathological differences have been reported between acute graft-versus-host disease (aGVHD) rash and non-aGVHD rash in CD34 +-selected peripheral blood stem cell transplantation (PBSCT) recipients, skin biopsy alone is usually insufficient to determine rash etiology. As such, distinguishing inflammatory non-aGVHD rashes, such as drug eruptions, from cutaneous aGVHD after CD34 +-selected PBSCT remains challenging and relies on clinical presentation. This study aimed to identify etiologies of skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…We reported a rate of 79% of patients with exanthema. Klager et al [6] reported a rate of 62% (152 of 243 patients) of skin rashes of any causes, only 17.7% being due to GvHD after T-cell depleted ASCT. The incidence of GvHD in non-T-cell-depleted ASCT is 40–60%, and about 70% of these patients have skin involvement [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We reported a rate of 79% of patients with exanthema. Klager et al [6] reported a rate of 62% (152 of 243 patients) of skin rashes of any causes, only 17.7% being due to GvHD after T-cell depleted ASCT. The incidence of GvHD in non-T-cell-depleted ASCT is 40–60%, and about 70% of these patients have skin involvement [49].…”
Section: Discussionmentioning
confidence: 99%
“…However, making a distinction between aGvHD of the skin and the competing diagnoses is difficult and mainly based on clinical findings, as no specific diagnostic markers for aGvHD are established [6]. The diagnostic value of skin histopathology is limited by the lack of specific diagnostic criteria [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allo-hematopoietic stem-cell transplantation (HSCT) patients are subjected to composite drug protocols, augmenting the risk for pruritus [ 156 ]. A report evaluated the possible causes of skin alterations in the first year after CD34+-selected peripheral blood stem cell transplantation (PBSCT) [ 157 ]. A retrospective study evaluated 243 subjects who experienced CD34+-selected PBSCT.…”
Section: Targeted Therapy and Pruritusmentioning
confidence: 99%
“…Single drug culprits were recognized in 51% of rashes. The most frequently described drugs comprised chemotherapy, antibiotics, keratinocyte growth factor, and recombinant IL-7 [ 157 ].…”
Section: Targeted Therapy and Pruritusmentioning
confidence: 99%